2018
DOI: 10.1096/fj.201800751r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Klotho on autophagy clearance in tacrolimus‐induced renal injury

Abstract: Recently, we showed that tacrolimus‐induced renal injury was closely associated with impairment of autophagy clearance, and Klotho deficiency aggravated tacrolimus‐induced renal injury. In this study, we evaluated the effect of Klotho treatment on autophagy clearance in tacrolimus‐induced renal injury. We evaluated the effect of Klotho on tacrolimus‐induced renal injury in an experimental mouse model and in vitro by treatment with tacrolimus and/or recombinant mouse Klotho. In vivo and in vitro studies showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Furthermore, urolithin A treatment enhanced TFEB expression, thus, promoting autophagy and ameliorating renal IR injury [183]. In immunosuppressant tacrolimus (Tac)-induced renal injury, impaired autophagy was found to be in tubules, which exhibited FoxO3-mediated autophagy associated with a reduction of TFEB [184]. In addition, Klotho protected Tac-induced renal injury by restoring lysosomal function and improving autophagy by inducing nuclear translocation of TFEB through inhibiting phosphorylation of glycogen synthase kinase 3β (GSK3β) [184].…”
Section: Tfeb-mediated Autophagy Induction and Renal Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, urolithin A treatment enhanced TFEB expression, thus, promoting autophagy and ameliorating renal IR injury [183]. In immunosuppressant tacrolimus (Tac)-induced renal injury, impaired autophagy was found to be in tubules, which exhibited FoxO3-mediated autophagy associated with a reduction of TFEB [184]. In addition, Klotho protected Tac-induced renal injury by restoring lysosomal function and improving autophagy by inducing nuclear translocation of TFEB through inhibiting phosphorylation of glycogen synthase kinase 3β (GSK3β) [184].…”
Section: Tfeb-mediated Autophagy Induction and Renal Injurymentioning
confidence: 99%
“…In immunosuppressant tacrolimus (Tac)-induced renal injury, impaired autophagy was found to be in tubules, which exhibited FoxO3-mediated autophagy associated with a reduction of TFEB [184]. In addition, Klotho protected Tac-induced renal injury by restoring lysosomal function and improving autophagy by inducing nuclear translocation of TFEB through inhibiting phosphorylation of glycogen synthase kinase 3β (GSK3β) [184]. A recent study has demonstrated TFEB-mediated autophagic clearance of proteolipid aggregates in a mouse model of Batten disease in mTORC1-independent and Akt-dependent manners [185].…”
Section: Tfeb-mediated Autophagy Induction and Renal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our previous study found that systemic administration of α-klotho had a pro-lipolytic effect on liver and the white adipose tissue (Rao et al, 2019). Furthermore, α-klotho has been demonstrated to have a protective effect on the heart and kidneys (Guo et al, 2018;Lim et al, 2018). Generally, there are two forms of αklotho, a full-length (130 kDa) and a shorter form (65 kDa) (Xu and Sun, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that Sirt1 has been regulating autophagy through the deacetylation of Atg5, Atg7, and Atg8 [224]. Autophagy extended the lifespan of mice knock-out Klotho [225], and Klotho attenuated renal lesions by regulating the autophagy clearance [226]. Based on these studies, we identified a key link between antiaging proteins like Sirt1, Klotho in DN, but further studies are still necessary to illustrate how the antiaging proteins regulate the autophagy and the exact sites for autophagy modulation.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%